Intra-articular injections in the treatment of osteoarthritis - Yu. A. Olyunin; I. N. Schendrigin (Современная ревматология)
Local methods are widely used in the treatment of osteoarthritis (OA) and play a significant role in the complex therapy of this disease. A special place among them belongs to intra-articular (i/a) administration of drugs. The most widely used for this purpose are glucocorticoids (GC) and hyaluronic acid (HA) drugs. When comparing the effectiveness of these drugs, it was shown that during the 1st month, HA had more favorable results, after 3 months the results did not differ significantly, and after 6 months, the effectiveness of HA was higher. Some authors believe that the optimal result can be obtained with the combined use of HA and GC.The efficacy and tolerability of HA drugs in patients with OA have been studied in numerous randomized controlled trials (RCTs), and the data obtained in these studies have been summarized in a number of meta-analyses. At the same time, both in RCTs and in meta-analyses, the results of such treatment were assessed differently. However, when summarizing the materials of various meta-analyses within the framework of a systematic review, it was shown that i/a injections of HA are an effective and safe method of local treatment of OA. However, there are no generally accepted recommendations for the use of HA in the treatment of OA, and the question of their administration in each case is decided individually, taking into account the history, clinical picture, OA phenotype, and tolerability of therapy. The Russian Association of Rheumatologists recommends the use of i/a HA injections in knee OA with synovitis and the use of HA injections to reduce pain and improve joint function.